Current Delimitation and Typology of the Czech Countryside and its Importance for Rural Development - Klufová, Renata (Eastern European Countryside, 2024)
The aim of the paper is to delimit the countryside in the Czech Republic (according to local conditions) and the rural municipalities’ typology (according to their development potential). The author also focuses on the usage of a combination of Geographic Information Systems, spatial data analysis, and spatial statistics tools, together with traditional multivariate statistical methods for rural delimitation and typology. The typology of the rural municipalities, according to their development potential, is based on up-to-date socio-economic indicators from the 2011 Census, which makes up the final part of the article, followed by conclusions and considerations about future rural development in the Czech Republic.